E-Commerce System for Media Group Cooperative - Mikha Melvin Agustian; Ririn Ikana Desanti; Wella Wella (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
E-Commerce is a way to shop online where it is easier for us to process transactions between sellers and buyers without having to face to face, at this time we are required to reduce face-to-face to reduce the spread of covid which is high. Based on these problems created a website that can make sales online. The method used in the system is the SDLC waterfall method to find suitable and appropriate features. The tools used are visual studio code, and Heidi SQL. The result of this research is the website is made using PHP, JavaScript, Bootstrap and CSS for the frontend and the backend of the website. The website created can help make sales online and reduce sales data loss in cooperatives.